2014
DOI: 10.1186/1752-1947-8-64
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastasis effectively treated with erlotinib following the acquisition of resistance to gefitinib: a case report

Abstract: IntroductionNon-small-cell lung cancer harboring an activated epidermal growth factor receptor mutation exhibits a good response to epidermal growth factor receptor-tyrosine kinase inhibitors; however, clinicians often experience treatment failure following the development of resistance to epidermal growth factor receptor-tyrosine kinase inhibitor.Case presentationWe here report a case of a 56-year-old Japanese woman with non-small-cell lung carcinoma with a secondary T790M mutation associated with resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Following the initial screening process, which involved removing ineligible articles and supplementing with studies from authors’ files, a total of 128 publications were ultimately included in the meta-analysis ( Appendix B and Appendix C ). 106 of the publications were case reports [ [14] , [15] , [16] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , …”
Section: Resultsmentioning
confidence: 99%
“…Following the initial screening process, which involved removing ineligible articles and supplementing with studies from authors’ files, a total of 128 publications were ultimately included in the meta-analysis ( Appendix B and Appendix C ). 106 of the publications were case reports [ [14] , [15] , [16] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , …”
Section: Resultsmentioning
confidence: 99%
“…Nanjo et al [43] described that acquired resistance to gefitinib is characterized by an upregulation of MET and absence of T790M mutation. Moreover, the T790M mutation has not been identified neither in BM or LM [44,45] , nor in CSF of patients who have developed LM following EGFR TKIs [46] . Jiang et al [47] reported a lower frequency of T790M mutation (21%) and a higher frequency of MET amplification (39%) in the CSF, suggesting that MET amplification could confer a major risk of leptomeningeal invasion [48] .…”
Section: Target Dosage/day Csf Level (Nmol/l) Penetration (Csf/plasmamentioning
confidence: 99%
“…But, there are also retrospective studies of patients with active CNS disease, both of brain metastases and leptomeningeal disease, who progressed on prior treatments with erlotinib or gefitinib but had intracranial response to afatinib [50]. Additionally, there have been reports of patients responding to erlotinib even after development of the T790M [51, 52]. We utilized pulse dosing for isolated CNS progression, as there is evidence that T790M mutations are less common in BrM during pharmacokinetic failure than in systemic disease [51].…”
Section: Systemic Therapymentioning
confidence: 99%